Completing the European Banking Union: Capital cost consequences for credit providers and corporate borrowers - Michael Koetter; Thomas Krause; Eleonora Sfrappini; Lena Tonzer (Halle Institute for Economic Research (IWH), 2021)
The bank recovery and resolution directive (BRRD) regulates the bail-in hierarchy to resolve distressed banks without burdening tax payers. We exploit the staggered implementation of the BRRD across 15 European Union (EU) member states to identify banks' capital cost and capital structure responses. In a first stage, we show that average capital costs of banks increased. WACC hikes are lowest in the core countries of the European Monetary Union (EMU) compared to formerly stressed EMU and non-EMU countries. This pattern is driven by changes in the relative WACC weight of equity in response to the BRRD, which indicates enhanced financial system resilience. In a second stage, we document asymmetric transmission patterns of banks' capital cost changes on to corporates' borrowing terms. Only EMU banks located in core countries that exhibit higher WACC are those that also increase firms' borrowing cost and contract credit supply. Hence, the BRRD had unintended consequences for selected segments of the real economy.
urn:nbn:de:gbv:3:2-134468
Keywords: C41; F34; G21; H63; 330; bail-in; banking union; funding costs; real effects